2013
DOI: 10.1002/j.1681-4835.2013.tb00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Online Social Networking on Youth: Case Study of Mauritius

Abstract: Online social websites have achieved a phenomenal global growth over the last decade, attracting much attention from researchers worldwide. It is a known fact that young adults and teenagers are the most avid users of such sites. Based on the findings of several research studies in the Online Social Networks (OSNs) area, it has been found that these OSN sites are having a great impact on the lives of young people. But since most of the research works were carried out in other countries, it was found necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Mauritian Internet users mostly use the medium for information search, communication and social media use (Gopee, 2016). According to previous studies, young people of age 14-35 years old are the highest user-group of social media, and it is estimated that on average, each young person spends more than 35 hours per month on social media sites such as Facebook (Chan-Meetoo & Rathacharen., 2011; Khedo et al, 2013). Moreover, Seebaluck et al (2015) found that the Mauritian family-related culture influenced the young people's purpose and amount of social media usage.…”
Section: Background: Mauritiusmentioning
confidence: 99%
“…Mauritian Internet users mostly use the medium for information search, communication and social media use (Gopee, 2016). According to previous studies, young people of age 14-35 years old are the highest user-group of social media, and it is estimated that on average, each young person spends more than 35 hours per month on social media sites such as Facebook (Chan-Meetoo & Rathacharen., 2011; Khedo et al, 2013). Moreover, Seebaluck et al (2015) found that the Mauritian family-related culture influenced the young people's purpose and amount of social media usage.…”
Section: Background: Mauritiusmentioning
confidence: 99%
“…6 Constantly navigating the stream of news from 'friends' on social media, including a large proportion whom they never met, especially young people feel constant pressure to live up to the same exhilarating experiences that these friends share. Reading what others are doing while being a bore at home feels unbearable for many (Kavi et al 2013). Two decades ago, bullying was limited to face to face and thus a relatively short time window; now that space has grown exponentially, in terms of time, space, and torture tools.…”
Section: From Blessing To Burdenmentioning
confidence: 99%
“…(Khedo, Suntoo, Sheik Mohammad, & Mocktoolah, 2013) examined the Impact of online social networking on Youth in Mauritius, the study shows how Mauritian youths are using online social networking on a large scale and their behavior and lifestyle. Another study reveals the preservation of the Indian diasporas' ancestral culture, languages, and identity in Mauritius as well as their participation in Mauritian society's broader socio-cultural, political, and economic spheres.…”
mentioning
confidence: 99%